Impact of patient isolation on emergency department length of stay: A retrospective cohort study using the Registry for Emergency Care. (9th September 2020) - O'Reilly, Gerard M; Mitchell, Rob D; Mitra, Biswadev; Noonan, Michael P; Hiller, Ryan; Brichko, Lisa; Luckhoff, Carl; Paton, Andrew; Smit, De Villiers; Cameron, Peter A
Abstract : A major burden of the COVID‐19 pandemic across Australian EDs is the large proportion of suspected COVID‐19 patients requiring isolation procedures. This first study using the Registry for Emergency Care clearly established that requiring isolation in an ED increases a patient's ED length of stay. Abstract: Objective: The number of patients with suspected COVID‐19 presenting to Australian EDs continues to impose a burden on healthcare services. Isolation is an important aspect of infection prevention and control, but has been associated with undesirable consequences among hospital inpatients. The aim of the present study was to determine if isolation is associated with an increased length of stay (LOS) in the ED. Methods: The Registry for Emergency Care Project is a prospective cohort study with a series of nested sub‐studies. The present study was a retrospective analysis of adult patients allocated an Australasian Triage Scale category of 1 or 2 who presented to a tertiary ED between 18 and 31 May 2020. The primary outcome was ED LOS. Regression methods were used to determine the independent association between ED isolation and LOS. Results: There were 447 patients who met inclusion criteria, of which 123 (28%) were managed in isolation. The median (interquartile range) ED LOS was 259 (210–377) min for the isolation group and 204 (126–297) min for the non‐isolation group, a difference in median ED LOS of 55 min ( P  < 0.001). Isolation was independently associated with a 23% increase in ED LOS ( P = 0.002) and doubled the odds of an ED stay of more than 4 h (adjusted odds ratio 2.2 [1.4–3.4], P = 0.001). Conclusion: Consistent with the anecdotal experience of Australian ED clinicians, the present study demonstrated an increased ED LOS for patients managed in isolation. Enhanced infection prevention and control precautions will be required during and beyond the current pandemic, creating significant ongoing challenges for emergency care systems.